ByzRev 05.2023.004: Philipp M. Forness – Alexandra Hasse-Ungeheuer – Hartmut Leppin (eds), The Good Christian Ruler in the First Millennium: Views from the Wider Mediterranean World in Conversation (Millennium-Studien 92). : Berlin – Boston: De Gruyter 2021. - Mösch, Sophia (The Byzantine Review, 2023)
Philipp M. Forness – Alexandra Hasse-Ungeheuer – Hartmut Leppin (eds), The Good Christian Ruler in the First Millennium: Views from the Wider Mediterranean World in Conversation (Millennium-Studien 92). Berlin – Boston: De Gruyter 2021. IX, 464 pp. – ISBN 978-3-11-072469-1 (€ 139.95)